2020
DOI: 10.1039/d0ra07733j
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast-charging and long cycle-life anode materials of TiO2-bronze/nitrogen-doped graphene nanocomposites for high-performance lithium-ion batteries

Abstract: The TiO2-bronze/nitrogen-doped graphene nanocomposites have the potential for fast-charging and have high stability, showing potential as an anode material in advanced power batteries for next-generation applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 95 publications
1
21
0
Order By: Relevance
“…Thus, the existence of a pseudo-capacitive channel in TiO 2 (B), which parallels to its layered perovskite structure, allows the possibility of fast Li-ion diffusion pathways across the structure of TiO 2 (B)-based nanocomposite electrodes. 42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the existence of a pseudo-capacitive channel in TiO 2 (B), which parallels to its layered perovskite structure, allows the possibility of fast Li-ion diffusion pathways across the structure of TiO 2 (B)-based nanocomposite electrodes. 42 …”
Section: Resultsmentioning
confidence: 99%
“…The specific capacity was then quickly raised to 400 mA h g –1 without loss of capacity when the current rate was returned to the starting rate of 50 mA g –1 , indicating outstanding rate capability and outstanding cycle performance. Thus, the existence of a pseudo-capacitive channel in TiO 2 (B), which parallels to its layered perovskite structure, allows the possibility of fast Li-ion diffusion pathways across the structure of TiO 2 (B)-based nanocomposite electrodes …”
Section: Resultsmentioning
confidence: 99%
“…Reduced graphene oxide (rGO) was synthesized via heat treatment at 800 °C for 5 hours in an inert atmosphere. 52 …”
Section: Methodsmentioning
confidence: 99%
“…Following that, the gradual weight loss over temperatures ranging from 150 °C to 300 °C indicated that the residual oxygen functions in NrGO had been decomposed. The samples lost some weight at temperatures ranging from 300 to 500 °C, which was attributed to the elimination of more permanent nitrogen-doped units in NrGO [31]. The substantial weight loss recorded over 500 °C appears to be particularly related to pyrolysis and carbonization of the carbon backbone chain, resulting in the emission of CO2.…”
Section: Ge/nrgo Nanocomposite Characterizationmentioning
confidence: 99%
“…The rGO was then homogeneously mixed with melamine (Aldrich, 99.9% analytical standard, MO, USA), which served as a nitrogen source. To produce the NrGO, the combined powder was annealed at 800 • C for 1 h in a nitrogen environment [31,32].…”
Section: Preparation Of Ge/nrgo Nanocompositesmentioning
confidence: 99%